Expert System Untuk Acupressure Dengan Metode Backward Chaining - Ratih Purwasih (Universitas Putra Indonesia YPTK Padang, 2019)
Acupressure or in other words called reflexology is a way of treating the disease through nerve center points associated with certain organs. In other words, healing is a disease through nerve massage to improve blood circulation. With the design of an expert acupressure system using foot massage created to help detect health problems experienced by someone by providing therapeutic solutions using foot reflexology in the form of graphics that must be massaged by the user without having to wait for help from people who are experts in their fields. The design of this system uses Backward Chaining inference, with the implementation of the system using the MySQL database system and Visual Basicprogram. From the system design that is made, it can be obtained a point massage solution that must be treated based on the symptoms felt.